PENGARUH PENYULUHAN TENTANG MAKANAN KARIOGENIK DENGAN METODE CERAMAH DAN DISKUSI TERHADAP PENGETAHUAN ANAK ANAK PENDERITA KARIES GIGI DI SDN 200208 KECAMATAN PADANGSIDIMPUAN SELATAN - Susi Febriani Yusuf; Juliana Lubis (Institut Pendidikan Tapanuli Selatan, 2022)
Clean and healthy behavior increasing effort have it purpose to raise the level of public health with personal hygiene as it priority for every ages classification, young or adult. Healthy and clean behavior can refers to teeth and mouth cleanliness which are part of body hygienity we can’t separate one each other because it influence to whole body cleanliness. Dental caries is one of the main problems in dental and mouth health, especially for elementary school children. It effect dental pain which can make decreasing appetite in a children, and finally it causes nutritional deficiency. The cariogenic food consumption is estimated can increase incidence of dental caries. One effort that can be done to improve children clean and healthy dental behavior knowledge and improving them healthiness is through health education by providing counseling of cariogenic food to preventing dental caries. This study aims to determine the influence of illumination with a lecture and discussion to improve the knowledge of children with dental cavity about cariogenic food in SDN 200220 sidimpuan city. This research was a quasi-experimental designed with one group pretest-posttest with 100 children as total sampling who detected have dental cavity. Amounting 100 student, 50 student to discuss group and 50 student to lecture group. Data obtained from the questionnaire questions. Test used paired sample t-test. The result showed that the average value of the highest knowledge in the group discussion method than the lecture method at 36,74. The test result test showed the method of discussion is more effective in improving knowledge of children about cariogenic food in SDN 068004. It is recommended to teacher and UKGS staff to prioritize discussion method as an alternative to the provision of information to improve the knowledge of children on SDN 068004.